(untitled) (Czech Journal of International Relations, 1967)
Relations between two neighboring states are always determined by a number of factors that reflect political decision-making by responsible officials in both states, but they are also strongly influenced by geographical location, historical traditions, the level of economic, political and cultural development achieved on both sides, and last but not least by the wider international constellation, i.e. the neighbors of these states . Enforcing the principles of friendship, undisturbed cooperation and internationalism is much easier in relations between states that do not have common borders than between neighboring states. No country can choose its neighbors, and many problems have been accumulated at almost every border in the recent past.